2015
DOI: 10.1109/tifs.2015.2398817
|View full text |Cite
|
Sign up to set email alerts
|

Deep Representations for Iris, Face, and Fingerprint Spoofing Detection

Abstract: Biometrics systems have significantly improved person identification and authentication, playing an important role in personal, national, and global security. However, these systems might be deceived (or "spoofed") and, despite the recent advances in spoofing detection, current solutions often rely on domain knowledge, specific biometric reading systems, and attack types. We assume a very limited knowledge about biometric spoofing at the sensor to derive outstanding spoofing detection systems for iris, face, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
248
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 485 publications
(265 citation statements)
references
References 70 publications
2
248
0
2
Order By: Relevance
“…Experiments showed that these approaches gained outstanding classification results for all problems and modalities in eight out of nine benchmarks. The results describe that spoofing detection systems based on convolutional networks are robust to known attacks and can be adapted to image based attacks [9].…”
Section: Literature Reviewmentioning
confidence: 89%
See 1 more Smart Citation
“…Experiments showed that these approaches gained outstanding classification results for all problems and modalities in eight out of nine benchmarks. The results describe that spoofing detection systems based on convolutional networks are robust to known attacks and can be adapted to image based attacks [9].…”
Section: Literature Reviewmentioning
confidence: 89%
“…David et al [9] investigated spoofing detection systems for different biometric modalities such as iris, face, and fingerprint based on two deep learning approaches. The first approach makes use of learning suitable convolutional network architectures for each domain and the second approach focuses on learning the weights of the network via back-propagation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, by using sensory data generated from an infrared distance sensor, a deep learning classifier was developed for fall detection especially amongst the elderly population [50]. Besides these, with respect to security, combining biometric sensors and CNNs has resulted in a more robust approach for spoofing and security breach detection in digital systems [51]. Yin et al [52] used a deep convolution network for proper visual object recognition as another application area of deep learning in the analysis of big sensed data, whereas for early detection of deforestation, Barreto et al [53] proposed using a multilayer perceptron technique.…”
Section: Deep Learning On Sensor Network Applicationsmentioning
confidence: 99%
“…Entretanto, apesar da certa dificuldade em fraudar tais mecanismos de segurança em comparação com os sistemas baseados em senhas e cartões, hoje, dada sua disseminação pela sociedade, criminosos já desenvolveram mecanismos de ataque capazes de driblar os sensores de captura das características biométricas, simulando traços de usuários válidos, técnica conhecida como spoofing (MENOTTI et al, 2015;SILVA;PAULINO, 2015). Frente a esta realidade, torna-se necessário o desenvolvimento de métodos preventivos, istoé, de contramedida.…”
Section: Introductionunclassified